IMPLEMENTING A SPIRITUAL LEADERSHIP: MORNING PRAYING LEADERSHIP - Iqbal Robbie (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
Sharia Credit Banks are alternative financial financing for communities other than conventional banks and other Islamic banks. BPRS Daya Artha Mentari carries out the mandate as a financial institution to serve the needs of the community in Islamic banking practices. These noble mandates and ideals are related to elements of philosophy, goals, processes and human resources that require the presence and need of leaders who have the ability, competence and high integrity to reach their ideal goals and expected goals. Based on his profile, the leadership in this bank has been proven by achieving success in delivering the bank as one of the banks that is leading the way in serving banking services in East Java. To strengthen the uniqueness of the research on leadership style in BPRS Daya Artha Mentari, it is necessary to state the description of the history of bank development and the accompanying leadership dynamics since its establishment in 1999. The history is divided into three development phases, namely the pioneering phase, the integration phase and the innovation phase. The results of this study can also be one of the models of leadership style in financial institutions and provide theorytical contributions to the development of science related to Human Resource Management, especially leadership style that is applied by the leaders of the sharia rural bank.